Independent Autonomic Modulation of Sinus Node and Ventricular Myocardium in Healthy Young Men During Sleep - KOWALLIK, PETER; BRAUN, CHRISTIAN; MEESMANN, MALTE (Journal of cardiovascular electrophysiology, 2000)
Autonomic Modulation of Sinus Node and Ventricle. Introduction. The aim of this study was to investigate whether autonomic modulation of ventricular repolarization may spontaneousiy differ from that of the sinoatrial node. Methods and Results. Onset of P waves. QRS complexes, and the apex and end of T waves were detected heat to heat in high‐resolution ECGs from nine healthy young men during the night. There were time‐dependent fluctuations in the QT/RR slopes of consecutive 5‐minute segments that could not he explained by the mean RR cycle length of the respective segment. Because the variahility found in QT intervals could not be explained hy either possible effects of rate dependence or hysteresis, autonomic effects were obvious. Power speetral analysis was performed for consecutive 5‐minute segments of PP and QT techograms. In a given subject. trends in the time course of low‐frequency (LF) and high‐frequency (HF) power in PP and QT often were similar, but they were quite different at other times. The mean LF/HF ratio for QTend (0.75 ± 0.1) was different from that of PP (1.8 ± 0.2; P = 0.002), indicating differences in sympathovagal balance at the different anatomic sites. Furthermore, at a given mean heart rate, averaged QT intervals were different on a time scale of several minutes to hours. The QT/RR slope of 5‐minute segments correlated significantly with the HF power of QT variability but not with that of PP variability, indicating effects of the autonomic nervous system on ventricular action potential restitution. Conclusion. These differences demonstrate that changes in sinus node automaticity are not necessarily indicative of the autonomic control of ventricular myocardium. (J Cardiavasc Electrophysiol, Vol. II, pp. 1063‐1070. October 2000)